Credit Constraints and Investment Behavior in Mexico’s Rural Economy - Love, Inessa; Sanchez, Susana M. (2012)
This paper uses two recently completed surveys of individual entrepreneurs (farmers and microentrepreneurs) and registered enterprises (agricultural and nonagricultural) operating in Mexico s rural sector to provide new evidence about the factors influencing the incidence of credit constraints and investment behavior. To measure the incidence of credit constraints, the authors use self-reported information on whether economic agents have a demand for loans, separating formal and informal markets. They define credit constraints as a situation where rural agents report an unsatisfied demand for loans (formal or informal), which originates from rural agents having projects that are too risky or from impediments hindering the ability of rural agents and lenders to reduce information asymmetries. The authors find that the self-reported demand for loans is low. Nevertheless, the incidence of credit constraints is pervasive, especially among individual entrepreneurs. The low use of loans has consequences for the amount of investments that occur in the rural economy, posing a major obstacle to Mexico s convergence towards its NAFTA partners. The empirical analysis, which includes proxies of business prospects and creditworthiness, shows that improving the availability of loans to credit constrained agents would increase the number of agents making investments and their investment to capital ratios.